Oral health services use among schoolchildren/teens with developmental disabilities in Colombia’s Capital District, 2015 - Rocha-Buelvas, Anderson Iván; Thomas-Alvarado, Yeily; Hidalgo-Troya, Arsenio (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: the use of oral health services is affected by aspects like age, sex, education, income, occupation, socioeconomic status, availability of services, geographic location, cultural aspects, attitudes towards health, values, lifestyles, previous health care experiences, presence or absence of symptoms, and disabilities. The aim of this study was to identify the determinants to oral health services use among a group of schoolchildren and adolescents with developmental disabilities in the city of Bogota (Colombia). Methods: a descriptive crosssectional study was conducted. A survey on determinants to the use of oral health services was applied to 102 parents of schoolchildren and adolescents with developmental disabilities in the city of Bogota (Colombia) during the first quarter of 2015 through probabilistic sampling. The inclusion criteria were as follows: parents in charge of schoolchildren and adolescents aged 4 to 18 years with an intellectual disability who were in cognitive, psychological and physical ability to respond. Bivariate and multivariate analysis were performed using the R software version 3.2.0. Results: there was a significant association between enabling factors like consulting for bleeding gums (p = 0.009), visiting a physician for dental problems (p = 0.081), knowledge of health rights (p = 0.001) or consulting the dentist for regular checkups (p = 0.006) and the use oral health services by schoolchildren and adolescents with developmental disabilities Conclusion: it is important to establish improvement strategies by articulating private or public health services providers with institutions devoted to the education of persons with disabilities, in order to reduce the access barriers in this minority group